Assessment of variability in temperature tolerance and antagonistic activity among Trichoderma isolates for biological control applications - S.S. Veena; Chithra Vinod; J. Sreekumar; S. Karthikeyan; M.L. Jeeva (JOURNAL OF ROOT CROPS, 2025)
Abstract Trichoderma is a well-known genus of fungi, widely recognized for its role in biocontrol within agricultural systems. These fungi are commonly found in the soil and root zones of plants, where they contribute to enhance plant health and control diseases caused by soil-borne pathogens. The use of Trichoderma, either alone or in combination with organic amendments, is recommended for managing major diseases in tropical tuber crops. These include tuber rot and stem and root rot in cassava, anthracnose in yam, collar rot and postharvest rot in elephant foot yam, and taro leaf blight. Understanding the environmental conditions, particularly temperature tolerance, is crucial to optimize the effectiveness of Trichoderma across different climates. The present study examined the variability in both antagonistic potential and temperature tolerance of 97 Trichoderma isolates collected from various regions across the country. The antagonistic potential was assessed against Sclerotium rolfsii, pathogen that causes collar rot in elephant foot yam. The isolates demonstrated a wide range of mycelial growth inhibition, from 66.11% to 100%, with 17 isolates achieving complete inhibition of S. rolfsii. All isolates were able to grow within a temperature range of 15°C to 35°C, with optimal growth observed at 30°C, followed by 35°C. Two isolates were capable of thriving at temperatures as high as 40°C indicating their valuable use in regions with extreme climatic conditions. This variation in antagonistic potential and temperature tolerance among the isolates is valuable for selecting and developing effective isolates for specific crops, pathogens, and regions